Regional Financial Management Policy that Implies To Criminal Administration - Sugianto Sug (Journal of Social and Development Sciences, 2017)
Abstract: Regional autonomy can not be separated from the issue of the financial capacity of each region. In the previous year, autonomy is always associated with Automoney, it means that the independence of region in organizing its authority can be measured from its ability to explore the sources of income of its own. The Act No. 33 of 2004 is very concerning about the financial balance and accountability between the central government and the region in particular. This study used qualitative method, where data sources are obtained through field observation and literature study. The accountability and regional financial control and procedures for regional goverment budget are very important, because corruption seems to have been pervasive in all aspects of life, including in the government system. The linkage of administrative law with criminal law can be understood because both of them are a public law and in the process of law enforcement, criminal sanctions (criminal law) used to strengthen sanctions in state administrative law. In this case the criminal law is used to enforce the norms in other fields of law, or in other words functionalize the criminal law in the field of law.Keywords: Regional Autonomy, Accountability, Government, Law